Manajemen Keperawatan IMPLEMENTASI RENCANA STRATEGIS PELAYANAN KEPERAWATAN DALAM PERSPEKTIF KEPEMIMPINAN KEPALA RUANGAN BERBASIS BUDAYA ORGANISASI DI RUMAH SAKIT BUNGA KOTA CITRA - Muhammad Saubari Azhar Noor; Wahyudin Wahyudin; Machli Riyadi (CNJ: Caring Nursing Journal, 2018)
Organizational culture in which there is a relationship between humans can cause why a strategy can be implemented in a hospital. Leadership as one aspect of human relations determines a strategic plan that is technically imperfect if implemented properly, it will get better results compared to a perfect strategic plan but only on paper. This study uses ethnographic studies to explore the implementation of the strategic plan of nursing services in the perspective of the leadership of the head of the room based on organizational culture at one hospital in Kalimantan. Data retrieval uses indepth interviews, observations, and documentation. The focus of this research is divided into subfocus procedures, personnel, strategies or methods, staff structuring, direction, leadership style, values, assumptions, artifacts, and rituals. The results of this study indicate that the organizational culture is less conducive due to members who are just waiting for instructions from the leadership resulting in the leadership of the head of the room in administrator style. Whereas the implementation of the strategic plan depends on how the human resources in the hospital carry it out, especially how the leadership.